Special low cost housing programme (1986 - 88). Study on its implementation and problems / Shaharil Hj. Abu Bakar - Abu Bakar, Shaharil (1987)
Objectives of the study 1. To study the iniplernentation and problems facing the SLCHP by considering the role and attitude of the public and private sectors towerds its implementation. 2. To determine the problems that might hinder the progress of the SLCHP and steps taken to remedy it, 3. To make conclusions on the study and thereafter giving recommendations that would hopefully be of some help in the implementation of the SLCHP.